Pengaruh lanjutan dosis pupuk kotoran ternak ayam terhadap pertumbuhan dan produksi rumput Brachiaria humidicola pada pemotongan kedua - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
The aim of this research were to know the effect of dosage chicken manure and want to know the dosage of chicken manure that giving the best result to growth and production Brachiaria humidicola at the second defoliation. These experiment were conducted at the experimental farm of Animal Husbandry Faculty, Palangka Raya Christian University. This research was designed by using Completely Random Design (CRD) with single factor experiment that is dosage of chicken manure (A), that is a0 = without chicken manure (control), a1 = 20 ton ha-1, a2 = 30 ton ha-1 and a3 = 40 ton ha-1. The result showed that the applications of dosage chicken manure giving the effect to the number of chicks (10 days, 20 days, 30 days and 40 days), the high of crop in 10 days and the production of Brachiaria humidicola. The treatment of dosage chicken manure 30 ton ha-1 and 40 ton ha-1 give the same effect to the production while dosage of chiken manure 40 ton ha-1 give the highest production of Brachiaria humidicola. Key words : Chicken manure, second defoliation, production